Pelatihan website Desa Bleber sebagai sarana akuntabilitas dan transparansi publik - Setyorini, Nurul; Sholeh, Khabib; Riyanto, Riko Oktavian; Agustina , Rizka Putri; Sumiyati; Pambudi, Nanda Dwi (Universitas Serang Raya, 2025)
The COVID-19 pandemic struck Indonesia, crippling various sectors of society. Signs of recovery from this downturn are starting to be felt in various regions across the country. With a spirit of collective recovery, IT Telkom Purworejo and its team aim to provide training and assistance related to technology. The theme chosen for the community service activity is